The effect of metformin-induced AMPK activation on adipogenesis and HIV replication - Alexandre, Kabamba Bankoledi (My University, 2008)
ABSTRACT Metformin is the most common drug used against type 2 diabetes mellitus. However, it was only recently shown, in human and rat hepatocytes, that metformin-like 5-aminoimidazole-4-carboximide ribonucleoside (AICAR), acts via activation of the AMP-activated protein kinase (AMPK), an enzyme that plays a central role in lipid metabolism. Although it is well known that metformin is used in the treatment of type 2 diabetes and results in significant fat loss, no study has investigated the effects of this drug on adipocytes. In this report I studied the effects of metformin on the formation of fat deposits in mouse 3T3-L1 preadipocytes, as well as its effects on the activation of AMPK in these cells. Our results suggested that metformin significantly inhibits the transformation of pre-adipocytes into adipocytes. This is achieved via the inhibition of intracellular lipid accumulation during adipogenesis. In addition to its inhibition of intracellular lipid accumulation, metformin induced a significant increase in the phosphorylation of AMPK. It has been shown that AMPK activation with AICAR results in the inhibition of the nuclear factor-κB (NF-κB) induced gene expression. Since NF-κB is the key nuclear factor used by HIV-1 during the initiation of its gene transcription, I investigated the possibility of inhibiting HIV-1 replication in U1 cells with metformin and AICAR. I observed that AICAR and metformin inhibit HIV-1 replication in U1 cells. This inhibition wasparalleled by the accumulation of NF-κB in the cytoplasm of AICAR and metformin treated cells, and at the same time by a significant decrease in the concentration of this nuclear factor in the nucleus of these cells. However, I failed to observe any phosphorylation of AMPK by metformin and AICAR in U1 cells. In conclusion, metformin inhibits adipogenesis in mouse adipocytes and this inhibition is likely to take place via the activation of AMPK. AICAR and metformin have inhibitory properties against HIV-1 replication. However, this inhibition does not seem to be by the activation of AMPK.
Keywords: AMP-activated protein kinase; metformin; AICAR; NF-KB